MAKNA SEMANTIK KONTEKS SOSIAL EKONOMI CERPEN “HAWA PANAS” KARYA SILVERSTER PETARA HURIT - Pilipus Wai Lawet Lawet; Karolinda Letek Karhi (LPPM Universitas Bina Bangsa, 2025)
This article aims to describe the semantic meaning of the socio-economic context of the short story